Saberes históricos e lugares de memória : estratégias didáticas para o ensino de história no município de Lucas do Rio Verde – MT - Dentz, Edson Von (2018)
The teaching of history can be approached, understood and presented in multiple ways, and the present dissertation and research proposes to present provocations and efforts in differentiated strategies to mobilize historical knowledge in memory spaces involving elementary school students II and high school of a general way. It is considered that the absence of historical sense permeates all spaces of daily life and the need to mobilize memory is beyond the school space or the teaching of history as a curricular component. It should be emphasized that the present research contemplates questions related to teaching in this discipline and resumes the valorization of memory. Thus, researching the local historical memory and cultural heritage of a particular place are important elements for teaching history. In this sense, the research question that mobilizes this study stands out: "What are the ways in which differentiated strategies in the teaching of history can provide the construction of historical knowledge in different spaces of memory? How different methodological forms can stimulate this construction? "The objective is to investigate different strategies of teaching history using the patrimony and urban symbols, understanding them as memory locations of the municipality of Lucas do Rio Verde - MT as a way of learning and to improve didacticpedagogical proposals in the basic education curriculum. Methodologically the research is characterized as exploratory, of a bibliographic and field character since it counts on the work of deepening a thematic exploring scientifically the object of study. It seeks references through the patrimonial education methodology and proposes to go to the field to verify new methodological possibilities for the teaching of history. It is defined as a case study and is configured as a qualitative nature. Thus, this study presents singular relationships with the possibility of making the investigative practice a qualification process of history teaching in education. It is hoped to contribute to the historical learning and to problematize the didactic practice in different environments and until then explored in an apprehensive and timid way. And, thus, to contribute to the formation of critical citizens who understand their environment as the generator of historical riches, configuring themselves as participants in the construction of the historical process, as well as of the teaching of history. In the face of this we carry out, analyze, reflect and present educational strategies that have contributed significantly to heritage education, integrating research, teaching practices, theories, contributing to the formation of knowledge and citizenship in our students.